A study on the interaction between cadmium and α‐chymotrypsin and the underlying mechanisms. Issue 2 (28th October 2018) - Wang, Jing; Zheng, Xiaolin; Wang, Weichao; Guo, Hongli; Liu, Rutao; Zong, Wansong
Abstract: Because cadmium might interact with proteins and, thus, exert toxicity in organisms, it is vital to understand the molecular mechanism of the interaction between cadmium and biologically relevant proteins as well as the structural and functional changes in these proteins. In this study, the interaction between α‐chymotrypsin (α‐ChT) and cadmium chloride (CdCl2 ) was investigated by performing enzyme activity determinations, multispectroscopic measurements, isothermal titration calorimetry, and molecular docking studies. It was demonstrated that CdCl2 binds to α‐ChT mainly via electrostatic forces with (21.0 ± 0.982) binding sites, leading to the increase of α‐helix and the decrease of β‐sheet. The interaction between CdCl2 and α‐ChT loosened the protein skeleton and increased the molecular volume of α‐ChT. CdCl2 first binds to the interface of α‐ChT and then interacts with the key residues His 57 or Asp 102 or both in the active sites, leading to the activity inhibition of α‐ChT under the exposure of high CdCl2 concentrations.